Living With Contradictions: The Dynamics of Senior Managers' Identity Tensions in Relation to Sustainability. (September 2015) - Allen, Stephen; Marshall, Judi; Easterby-Smith, Mark
In this article, we investigate how senior managers located in Northern Europe in the energy and power industry coordinate their recognition of sustainability challenges with other things they say and do. Identity theory is used to examine the fine-grained work through which the managers navigate identities and potentially competing narratives. In contrast with other studies we find that pursuing cohering identities and resolving potential tensions and contradictions does not appear to matter for most of the managers. We explore the dynamics of how managers live with apparent contradictions and tensions without threat to their narrative coherence. We extend existing research into managerial identities and sustainability by showing how managers combine different potentially contrasting identity types, identifying nine discursive processes through which the majority of managers distance and deflect sustainability issues away from themselves and their companies, and, showing the contrasting identity dynamics in the case of one manager to whom narrative coherence becomes important and prompts alternative action.